O pensamento matemático no período pré-escolar - Hunhoff, Alice Regina (2023)
The subject of this research is mathematics in the pre-school period. It is a bibliographical study, with a qualitative approach, based on the Historical-Cultural Theory. It is part of the Research Line Culture, Educational Processes and Teacher Training of the Postgraduate Program in Education in Francisco Beltrão, at the State University of Western Paraná - UNIOESTE, and is part of the studies carried out by the Research Group on Teaching, Learning and Cultural-Historical Theory (GEPEATH). Through it, we seek to understand the development of mathematical thinking in children aged three to five. To achieve our objective, we highlighted the importance of researching and establishing relationships between mathematics and the pre-school period, based on the results of the literature review carried out and the social relevance of the research, indicated by the quality indicators of Brazilian education: Functional Literacy Indicator (INAF) and Basic Education Development Index (IDEB). We understand how children between the ages of three and five learn and develop, addressing the periodization of child development, the role of practical activity, the child's experiences, the teacher's intentional and systematic planning, mediation and the main activity that make up the defined age group. Next, we highlight the formation of concepts and the corresponding level, the characteristics of the development of thinking in children aged between three and five, the role of empirical thinking, the importance of questions and situations emerging from everyday life in the educational context, presenting the actions considered essential for developing preschoolers' thinking. Based on this, we establish relationships between the three ideal fields of mathematics to be worked on in the preschool period, namely numerical, spatial and measurement, with the principles found. We also sought to integrate theory and practice by thinking of teaching strategies that would promote omnilateral development for children aged three to five. As a result, we found that although mathematical thinking is not consolidated in Early Childhood Education, it is at this stage that the foundations that enable its formation are established, and it happens through three main categories: practical activity, intentional and systematized planning, and experience. These three categories are interconnected and work together to establish the foundations of mathematical thinking in children. We believe that understanding how thinking develops at this early stage of education enables intentional and systematic planning. This allows for pedagogical action aimed at achieving the objectives that are reached through practical activities that are linked to the child's main activity and signified in their experiences. These, in turn, guide intentional planning and practical activities. Therefore, together, these categories play a fundamental role in promoting and realizing the development of the foundations of mathematical thinking, enabling effective and meaningful learning in the area of mathematics in the early years of elementary school. Finally, we suggest further research into the development of preschoolers' mathematical thinking, with the aim of building knowledge collaboratively in this area that is so important for education.